New approaches in bioprocess‐control: Consortium guidance by synthetic cell‐cell communication based on fungal pheromones. Issue 6 (14th April 2018) - Hennig, Stefan; Wenzel, Mandy; Haas, Christiane; Hoffmann, Andreas; Weber, Jost; Rödel, Gerhard; Ostermann, Kai
Abstract: Bioconversions in industrial processes are currently dominated by single‐strain approaches. With the growing complexity of tasks to be carried out, microbial consortia become increasingly advantageous and eventually may outperform single‐strain fermentations. Consortium approaches benefit from the combined metabolic capabilities of highly specialized strains and species, and the inherent division of labor reduces the metabolic burden for each strain while increasing product yields and reaction specificities. However, consortium‐based designs still suffer from a lack of available tools to control the behavior and performance of the individual subpopulations and of the entire consortium. Here, we propose to implement novel control elements for microbial consortia based on artificial cell–cell communication via fungal mating pheromones. Coupling to the desired output is mediated by pheromone‐responsive gene expression, thereby creating pheromone‐dependent communication channels between different subpopulations of the consortia. We highlight the benefits of artificial communication to specifically target individual subpopulations of microbial consortia and to control e.g . their metabolic profile or proliferation rate in a predefined and customized manner. Due to the steadily increasing knowledge of sexual cycles of industrially relevant fungi, a growing number of strains and species can be integrated into pheromone‐controlled sensor‐actor systems, exploiting their unique metabolic properties for microbial consortia approaches.